PENGARUH DISIPLIN, MOTIVASI KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI TENAGA KERJA OUTSOURCING (TKO) PADA SATUAN KERJA PUSAT PROGRAM TRANSFORMASI BANK INDONESIA - Acep; Ramadhani Hamzah; Riduan Siagian (Jurnal Ekonomi Bisnis Indonesia, 2020)
The purpose of this study was to determine the effect of variables of discipline, jobmotivation, compensation and employee performance. Test results partially for disciplinaryvariables with a statistic value of tcount> t table (4.258> 1.985) and a probability value of 0.000 <0.05, then Ho is rejected means there is a significant effect of the discipline variable on employeeperformance. Partial test results for job motivation variables with a statistic value of t count> t table(1.207 <1,985) and a probability value of 0.207 > 0.05, then Ho is accepted means that there is nosignificant effect of work motivation variables on employee performance. Partial test results forcompensation variables with a statistic value of t count> t table (3.613 > 1.985) and a probabilityvalue of 0.000 < 0.05, then Ho is rejected means that there is a significant effect of the compensationvariable on employee performance. Simultaneous test results with a value of Fcount > Ftable(30.234> 2.70), then Ho is rejected or Ha is accepted which means that there is a significantsimultaneous influence (together) of the variables of discipline, work motivation, and compensationtogether towards variable employee performance.